Epidemiologic Investigation of a Cluster of Deaths due to Eating Fried Rice Balls Intentionally Tainted with Quinalphos, Sironko District, Uganda, a case series, 2017 - Patricia Eyu; Denis Nixon Opio; Alex Riolexus Ario (Journal of Interventional Epidemiology and Public Health)
BACKGROUND: Quinalphos is an organophosphate chemical chiefly used as a pesticide. On 13 November 2017, a cluster of unexplained deaths was reported in Village X, Sironko District, Eastern Uganda. We investigated to identify the scope and exposures for the cluster of deaths, and recommend control-measures.